Internationalization within higher education and its influence on faculty: experiences of Turkish academic staff - Bedenlier, Svenja (Journal of Research in International Education, 2017)
In this article, findings are reported from a phenomenology-oriented study on prolonged international mobility and the effects of internationalization on the professional lives of six academic faculty at a Turkish research university. Drawing on research on international mobility of faculty and the present context of Turkish higher education, this investigation identifies three distinct phases of the sojourn abroad – motivation to go abroad, being abroad, repatriating to Turkey – being framed by the supportive and demanding culture of the specific institution. For the participants, ambivalently perceived effects at the individual, institutional and national level include networks gained, the imperative to publish in English, and the lack of a comprehensive national policy for internationalizatio
Keywords: center and periphery; academic faculty; Turkey; Internationalization of higher education